2007
DOI: 10.1159/000110021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Salt on Intrarenal Angiotensin System, NAD(P)H Oxidase, COX-2, MCP-1 and PAI-1 Expressions and NF-κB Activity in Salt-Sensitive and -Resistant Rat Kidneys

Abstract: Background: Chronic consumption of a high-salt diet causes hypertension (HTN) and renal injury in Dahl salt-sensitive (SSR) but not salt-resistant rats (SRR). These events are, in part, mediated by oxidative stress and inflammation in the kidney and vascular tissues. Activation of the angiotensin II type 1 (AT1) receptor plays an important role in the pathogenesis of oxidative stress and inflammation in many hypertensive disorders. However, the systemic renin-angiotensin system (RAS) is typically su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 82 publications
6
56
1
1
Order By: Relevance
“…Hypertension increases endothelial oxidative stress and inflammation and leads to worse stroke outcomes and higher mortality [210][211][212][213][214][215][216][217][218][219][220]. Studies investigating the underlying pathophysiology of hypertension indicates the involvement of neuroimmune interactions.…”
Section: Hypertensionmentioning
confidence: 99%
“…Hypertension increases endothelial oxidative stress and inflammation and leads to worse stroke outcomes and higher mortality [210][211][212][213][214][215][216][217][218][219][220]. Studies investigating the underlying pathophysiology of hypertension indicates the involvement of neuroimmune interactions.…”
Section: Hypertensionmentioning
confidence: 99%
“…LOX and COX produce oxidative stress through NAD(P)H oxidase-dependent and -independent pathways (29,195). Ang II treatment of rat aortic smooth muscle cells induced 5-lipoxygenase (5-LOX), resulting in an increased production of leukotriene B(4) [LTB(4)].…”
Section: Lipooxygenases (Lox) and Cyclooxygenases (Cox)mentioning
confidence: 99%
“…In addition, dietary salt increases the glomerular expression of TGF-b1 on renal tissue and also, augments nitric oxide production (14). High salt intake also induces the intrarenal aldosterone receptor and promotes renal fibrotic injury (15). Two recent studies identified that increased dietary salt intake promotes tissue inflammation by triggering IL-17-producing CD4 + T cell development (16,17).…”
Section: Introductionmentioning
confidence: 99%